Modifications in Wheelchair Propulsion Technique with Speed - Russell, Ian M.; Raina, Shashank; Requejo, Philip S.; Wilcox, Rand R.; Mulroy, Sara; McNitt-Gray, Jill L. (Frontiers in Bioengineering and Biotechnology, 2015)
Objective: Repetitive loading of the upper limb joints during manual wheelchair propulsion has been identified a factor that contributes to shoulder pain, leading to loss of independence and decreased quality of life. The purpose of this study was to determine how individual manual wheelchair users with paraplegia modify propulsion mechanics to accommodate expected increases in reaction forces generated at the pushrim with self-selected increases in wheelchair propulsion (WCP) speed. Methods: Upper extremity kinematics and pushrim reaction forces were measured for 40 experienced manual wheelchair users with paraplegia while propelling on a stationary ergometer at self-selected free and fast propulsion speeds. Upper extremity kinematics and kinetics were compared within-subject between propulsion speeds. Between group and within subject differences were determined (α =0.05). Results: Increased propulsion speed was accompanied by increases in Reaction Force (RF) magnitude (22 of 40, >10N) and shoulder Net Joint Moment (NJM, 15 of 40, >10Nm) and decreases in pushrim contact duration. Within-subject comparison indicated that 27% of participants modified their WCP mechanics with increases in speed by regulating RF orientation relative to the upper extremity segments. Conclusions: Reorientation of the RF relative to the upper extremity segments can be used as an effective strategy for mitigating rotational demands (NJM) imposed on the shoulder at increased propulsion speeds. Identification of propulsion strategies that individuals can use to effectively accommodate for increases in RFs is an important step towards preserving musculoskeletal health of the shoulder and improving health-related quality of life.